2012
DOI: 10.1007/s13337-012-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Host and Virus Protein Interaction Studies in Understanding Shrimp Virus Gene Function

Abstract: Protein-protein interaction studies have been widely used in several fields to characterize an unknown protein. This in turn helps to find out several pathways to understand a complex mechanism or discover a drug for treatment. Among the methods, yeast two-hybrid has widely been used in human, animal and plant research studies. This aspect of research has also been found useful in understanding the shrimp virus gene function. With respect to White spot syndrome virus, interaction studies have been applied to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…These results suggest that binding of SG with the virus is both necessary and dependent on the sulfate groups (Talarico et al, 2004;Matsuhiro et al, 2005;Chattopadhyay et al, 2007). (Zhou et al, 2009;Otta, 2012). The envelope protein VP 26 has been identified as a tegument protein which is supposed to be associated with viral penetration due to its actin binding motif that facilitates the attachment of the virus to the shrimp cell membrane Tsai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that binding of SG with the virus is both necessary and dependent on the sulfate groups (Talarico et al, 2004;Matsuhiro et al, 2005;Chattopadhyay et al, 2007). (Zhou et al, 2009;Otta, 2012). The envelope protein VP 26 has been identified as a tegument protein which is supposed to be associated with viral penetration due to its actin binding motif that facilitates the attachment of the virus to the shrimp cell membrane Tsai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Far-Western blot analysis demonstrated that SG bound to the envelope proteins of WSSV, including VP 24, VP 26, VP 28, VP 31 and VP 39, although only the binding of SG with VP 26 and VP 28 was confirmed. It has been revealed that four major WSSV envelope proteins, VP 19, VP 24, VP 26 and VP 28, form a multiprotein complex for the virus infection process (Zhou et al , 2009; Otta, 2012). The envelope protein VP 26 has been identified as a tegument protein which is supposed to be associated with viral penetration due to its actin binding motif that facilitates the attachment of the virus to the shrimp cell membrane (Xie & Yang, 2005; Tsai et al , 2006).…”
Section: Discussionmentioning
confidence: 99%